Swietenia mahogany Jacq. (Meliaceae) seeds were extracted with methanol. In choice and no-choice leaf disc methods, the crude extract at 5% completely inhibited feeding activity of third instar larvae of the diamondback moth, Plutella xylostella (L.) (Lepidoptera: Yponomeutidae). Fractionation of the extract by combination of counter-current distribution method, silica gel column chromatography and preparative TLC yielded one fraction which strongly inhibited P. xylostella larval feeding activit - Dadang .; Kanju Oshawa (Buletin Hama dan Penyakit Tumbuhan, 2000)
Swietenia mahogany Jacq. (Meliaceae) seeds were extracted with methanol. In choice and no-choice leaf disc methods, the crude extract at 5% completely inhibited feeding activity of third instar larvae of the diamondback moth, Plutella xylostella (L.) (Lepidoptera: Yponomeutidae). Fractionation of the extract by combination of counter-current distribution method, silica gel column chromatography and preparative TLC yielded one fraction which strongly inhibited P. xylostella larval feeding activity by 98.3 % at a concentration of 0.2%.